The Impact of Industry 4.0 on Supply Chain Management - Nivit Nair; Praveena T (International Journal of Supply Chain Management, 2021)
This paper covers how the technologies used in Industry 4.0 will play a major role in the development of Supply Chain Management. Industry 4.0 includes technologies such as Internet of Things (IoT), Big Data Analytics, Smart Factory, Cyber Physical Systems, Blockchain and Machine Learning. With digitization being adopted by various Supply Chain Industries, the above mentioned technologies will play a key role in different phases of a Supply Chain network such as manufacturing, procurement, logistics, warehousing and fulfillment.